Selector’s Guide for Resources in the Humanities: An Open Access Student Publication - Spurlock, Patrick; McNeal, Richard; Kidd, Rebecca; Lord, Bonnie; Day, Ashley; Dodd, Brian; Williams, Jessica; Baron, Courtney; Weeks, Thomas; Warner-Evans, Natalie; Fountain, Amy; Stokes, Teresa; et al. (My University, 2014)
Students in the Master of Library and Information Science degree program at Valdosta State University who completed the elective course in Humanities Information Services in 2014 produced bibliographies on sub-disciplines of the humanities. These example bibliographies are compiled into the document titled Selector’s Guide for Resources in the Humanities: An Open Access Student Publication. The student authored sections of the Selector’s Guide focus on narrowly defined humanities areas and contain resources representative of professional organizations, major serials, online indexes and databases, primary sources, classic and contemporary monographs, standard reference works, vetted websites, media, and open access resources. The compilers of this guide offer it as a companion to the document entitled Teaching Guide for Resources in the Humanities: An Open Access Publication. The Teaching Guide references two tutorials, one on WorldCat and one on the Gale Literary Index. Copies of both tutorials are found in here. The authors of these materials invite professors seeking a guide to the providers and formats of information in the humanities to use the bibliographies therein as a starting point for creating assignments and to use materials from the teaching guide as class exercises, if appropriate.